Kewarganegaraan dan Hak Konsumen Dalam Era Digital Economy: Perspektif Hukum Nasional - Zahra Nur Fadzilah; Ikhwanudin Alya Rahman; Salwa Nafiah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The rapid rise of Indonesia’s digital economy is changing how people participate as citizens and how their consumer rights are protected. This study explores the legal dimensions of digital citizenship through a normative juridical review of the Consumer Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law. Although these laws provide basic safeguards, significant problems remain such as data privacy violations, unclear algorithmic practices, cross-border legal barriers, and deceptive online advertising. Low public legal awareness and the absence of a unified dispute-resolution system further leave consumers vulnerable to powerful global digital platforms. The study argues that stronger protection requires embedding digital citizenship principles into Indonesia’s legal framework, harmonizing national rules with international standards, enhancing platform oversight, and improving digital literacy. In conclusion, a flexible and forward-looking legal approach is crucial to making consumer protection a core part of digital citizenship and ensuring public trust and human rights in the digital era.